Neither naked nor sacred : a theology for the public square: The Irish Catholic Church in the Republic of Ireland - Stanton, Carol A. (Trinity College (Dublin, Ireland). School of Hebrew, Biblical and Theological Studies, 2001)
Introduction: The Roman Catholic Church in Ireland, accustomed from the genesis of the Republic to a "special position," has been experiencing the loss of that privileged status. In the growing pluralism of the Republic some argue that, for the sake of that pluralism, all faith traditions should go private, that the "sacred" square should go "naked", to borrow from a phrase coined by Richard John Neuhaus. In the wake of the recent publicity about its clergy sexual abuse cases there is also some internal pressure within the Irish Catholic church to "go quiet." But the role of the Irish Catholic church is complex. Historically, it has been a source of identity and cohesion in the face of colonial oppression. Along with the State it shaped the ideologically conservative and certain world view out of which the Republic lived until the latter part of the twentieth century. This social cohesiveness, however, was gained at the price of an often harsh control and the failure to nurture a critically thinking public. More fundamental for the Irish Catholic church is that living at the heart of Christianity is a public mission, one which calls the church to live and preach the gospel, to be communicatively engaged at the centres of thought and hfe. To go private or quiet is to abandon that mission.
Keywords: Hebrew Biblical and Theological Studies, Ph.D.; Ph.D. Trinity College Dublin